Ethnic and socio-economic differences in the prevalence of wheeze, severe wheeze, asthma, eczema and medication usage at 4 years of age: Findings from the Born in Bradford birth cohort. (October 2016) - Petherick, Emily S.; Pearce, Neil; Sunyer, Jordi; Wright, John
Abstract: Background: Asthma, wheeze and eczema are common in early childhood and cause considerable morbidity. Generally rates of these conditions are higher in high income compared to low income countries. Rates in developed nations are generally higher than in less developed countries. After migration to Western countries, differences in risks of developing these conditions may between migrant and non-migrant may diminish. Methods: A convenience sample of 1648 children of White British, Pakistani or Other ethnicity aged between 4 and 5 years were recruited from the main Born in Bradford cohort. Children's parents or guardians were asked to report on a range of potential risk factors and their associations with wheeze, asthma and eczema. Relationships between ethnicity and disease outcomes were examined using logistic regression after adjustment for other relevant risk factors and confounders. Results: Ethnic differences in doctor diagnosed asthma were evident, with children of other ethnic Origin being less likely and children of Pakistani origin more likely to have a diagnosis than White British or other origin children, although after adjustment for other risk factors this difference only remained significant for the Other Ethnic group. Ethnic differences were not observed in other outcomes including wheeze in the past 12 months, severe wheeze and taking medications for breathing problems. Conclusions: In UK born children, traditional risk factors such as gender, family history, socio-economic status and child's medical history may be stronger risk factors than ethnicity or familial migration patterns. Highlights: Comparison of ethnic differences wheeze, asthma eczema and medication usage. Children of Other ethnic origin were less likely to have a doctor diagnosis of asthma. Other outcomes including severe wheeze, wheeze in the past 12 months, eczema or medication usage did not differ by ethnicity.